2020
DOI: 10.1155/2020/7060812
|View full text |Cite
|
Sign up to set email alerts
|

Bupleurum chinense Polysaccharide Improves LPS‐Induced Senescence of RAW264.7 Cells by Regulating the NF‐κB Signaling Pathway

Abstract: Macrophages are important inflammatory cells that play a vital role in inflamm-aging. Bupleurum chinense polysaccharide (BCP), an effective component of the Bupleurum chinense herb, exerts multiple beneficial pharmacological effects, such as improving immunity and antioxidant activity. However, the effects of BCP on macrophage-aging and inflamm-aging are yet to be established. In this study, we examined the effects of BCP on proliferation, inflammatory cytokines, β-galactosidase (SA-β-gal), senescence-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Although the monosaccharide types of different VBCPs are similar, the ratios are different, which provides the basis for different activities. Surprisingly, although VBCP-HW showed comparable activity with the data in the literature, 7 , 37 40 other methods such as UA, CA, and KA exhibited an excellent anti-inflammatory effect at the dose of 1 μg/mL, a far lower dose than that in the literature; additionally, the inhibiting ratio on TNF-α increased from 39% of VBCP-HW to 91.6% of VBCP-KA (1 μg/mL), which was slightly higher than that of the positive control. Meanwhile, as a typical anti-inflammatory cytokine, IL-10 plays a key role in innate immunity and is usually an immune-enhancing factor.…”
Section: Discussionsupporting
confidence: 69%
“…Although the monosaccharide types of different VBCPs are similar, the ratios are different, which provides the basis for different activities. Surprisingly, although VBCP-HW showed comparable activity with the data in the literature, 7 , 37 40 other methods such as UA, CA, and KA exhibited an excellent anti-inflammatory effect at the dose of 1 μg/mL, a far lower dose than that in the literature; additionally, the inhibiting ratio on TNF-α increased from 39% of VBCP-HW to 91.6% of VBCP-KA (1 μg/mL), which was slightly higher than that of the positive control. Meanwhile, as a typical anti-inflammatory cytokine, IL-10 plays a key role in innate immunity and is usually an immune-enhancing factor.…”
Section: Discussionsupporting
confidence: 69%
“…113 Bupleurum chinense polysaccharides improve the LPS-induced senescence of RAW 264.7 cells by regulating the NF-κB signaling pathway. 114 DOPs could reduce proinflammatory cytokines (TNF-α, IL-6) and MDA levels and improve estradiol, SOD, GSH-Px, T-AOC, and IL-10 levels in serum and alleviate the damage caused by aging through the inhibition of the NF-κB and p53/Bcl-2-mediated signaling pathways, suggesting that DOP may be a promising drug for treating premature ovarian failure (POF) caused by natural aging in females. 115 Xu et al found that Schisandra chinensis (Turcz.)…”
Section: Insulin/insulin-like Growth Factor-1 (Insulin/igf-1) Signali...mentioning
confidence: 99%